Psychological diagnostics in the talent development program of the German Football Association: Psychometric properties of an Internet-based test battery - Feichtinger, P.; Höner, O. (Sportwissenschaft, 2014)
The present study analyzes whether a multifaceted, football-specific and age-appropriate, Internet-based test battery in the talent development program of the German Football Association has acceptable psychometric properties in terms of reliability and validity. Additionally, the manuscript examines if this survey is affected by socially desirable responding (SDR). The study sample consists of male players within the U12 to U15 age groups. The psychological diagnostics capture personality characteristics assigned to motivation, volition, self-referential cognition, and emotion. A consistency analysis shows satisfying statistical values of Cronbach`s alpha, average inter-item correlation and corrected item-total correlation coefficients. Valid relationships between the psychological constructs were found. For the purpose of criterion validation, the comparison between a subgroup that was selected to a higher performance level and the total group of players illustrates the personality characteristics` relationship with football performance. A comparison between an anonymous and personalized group as well as correlation of SDR scales with the psychological tests does reveal small effects of social desirability that should be further considered. These findings demonstrate a scientifically sound assessment of the personality characteristics within talented football players. Further research on the characteristics` stability and prognostic power is needed to apply these diagnostics in order to support youth development in football. Die vorliegende Studie untersucht, ob eine multidimensionale, fußballspezifische und altersgerechte Online-Testbatterie im Talentförderprogramm des Deutschen Fußball-Bundes akzeptable Gütekriterien der Reliabilität und Validität aufweist. Zusätzlich wird überprüft, inwiefern die Befragung durch sozial erwünschtes Antwortverhalten (SEA) beeinflusst wird. Die Stichprobe der Studie umfasst männliche Spieler der Altersgruppen U12 bis U15. Die psychologische Diagnostik erhebt Persönlichkeitsmerkmale aus den Bereichen Motivation, Volition, selbstbezogene Kognition und Emotion. Eine Konsistenzanalyse zeigt zufriedenstellende Werte von Cronbachs Alpha, mittlerer Inter-Itemkorrelation und Trennschärfe. Zwischen den psychologischen Konstrukten wurden valide Zusammenhänge gefunden. Zum Zweck der Kriteriumsvalidierung lässt der Vergleich zwischen einer Teilgruppe, die für ein höheres höheresLeistungsniveau selektiert wurde, und der Gesamtgruppe von Spielern einen Bezug der Persönlichkeitsmerkmale zur Leistung im Fußball erkennen. Für den Vergleich zwischen einer anonymen und personalisierten Gruppe sowie für die Korrelation von SEA-Skalen mit den psychologischen Testverfahren resultieren geringe Effekte sozialer Erwünschtheit, die es weiterhin zu berücksichtigen gilt. Diese Erkenntnisse zeigen, dass die Persönlichkeitsmerkmale von talentierten Fußballspielern wissenschaftlich fundiert erfasst werden können. Für eine Anwendung der Diagnostik zur Unterstützung der Nachwuchsförderung im Fußball bedarf es weiterer Forschung zur Stabilität und Vorhersagegüte dieser Merkmale.